Transparency of Local Financial Management: Evidence from Local Governments in Indonesia - Toni Nurhadianto; Slamet Sugiri (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTThis study aims to provide empirical evidence about the influence of political competition, local independence, level of human development, and Supreme Audit Board (BPK) audit opinion on increasing transparency in local financial management in Indonesia. The research sample consisted of 436 local governments in Indonesia in 2016. The analytical method used to test the hypothesis is multiple linear regression. This study shows that local independence, level of human development, and BPK audit opinion have been proven to have a positive effect on increasing transparency in local financial management in Indonesia. On the other hand, political competition does not affect increasing transparency in local financial management in Indonesia. The results indicate that future studies should consider other factors to obtain more complete results. These include local government size, local expenditure, local government wealth, legislative size, local government complexity, level of dependence, local government financial capacity, press visibility, and local government administrative age. The findings contribute to the fundamental idea and recommendation for the government to improve Indonesia’s local financial management transparency. Keywords : Transparency, local financial management, local government ABSTRAKPenelitian ini bertujuan untuk memberikan bukti empiris tentang pengaruh persaingan politik, kemandirian daerah, tingkat pembangunan manusia, dan opini audit Badan Pemeriksa Keuangan (BPK) terhadap peningkatan transparansi pengelolaan keuangan daerah di Indonesia. Sampel penelitian terdiri dari 436 pemerintah daerah di Indonesia pada tahun 2016. Metode analisis yang digunakan untuk menguji hipotesis adalah regresi linier berganda. Hasil penelitian ini menunjukkan bahwa kemandirian daerah, tingkat pembangunan manusia, dan opini audit BPK terbukti berpengaruh positif terhadap peningkatan transparansi pengelolaan keuangan daerah di Indonesia. Di sisi lain, persaingan politik tidak mempengaruhi peningkatan transparansi pengelolaan keuangan daerah di Indonesia. Temuan penelitian ini berkontribusi dijadikan sebagai gagasan dan rekomendasi mendasar bagi pemerintah untuk meningkatkan transparansi pengelolaan keuangan daerah di Indonesia. Kata Kunci : Transparansi, tatakelola keuangan daerah, pemerintah daerah